The Effect of Brand Ambassador and Tagline on Brand Awareness on Sr12 Skin Care Products - Supriyadi Supriyadi; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (Peneliti.net, 2022)
This study aims to: To determine the effect of Brand Ambassador on Brand Awareness on Sr12 Skin Care products, a study in the Purwakarta Village Community, Purwakarta District, Cilegon City. To determine the effect of the Tagline on Brand Awareness on Sr12 Skin Care products, a study was conducted in the Purwakarta Village Community, Purwakarta District, Cilegon City. To determine the effect of Brand Ambassador and Tagline simultaneously on Brand Awareness on Sr12 Skin Care products, a study was conducted in the Purwakarta Village Community, Purwakarta District, Cilegon City. The research method used in this study used a survey method, while the target in this study were Sr12 skincare consumers in Indonesia Purwakarta Village, Purwakarta District, Cilegon City.with an unlimited population. The number of samples determined by this research amounted to 88 people according to Maholtra's opinion. Based on the results of the research